Cartier's hope : a novel - Rose, M. J., 1953- (Atria Books, 2020)
New York, 1910: A city of extravagant balls in Fifth Avenue mansions and poor immigrants crammed into crumbling Lower East Side tenements. A city where the suffrage movement is growing stronger every day, but most women reporters are still delegated to the fashion and lifestyle pages. But Vera Garland is set on making her mark in a man<U+2019>s world of serious journalism. Shortly after the world-famous Hope Diamond is acquired for a record sum, Vera begins investigating rumors about schemes by its new owner, jeweler Pierre Cartier, to manipulate its value. Vera is determined to find the truth behind the notorious diamond and its legendary curses<U+2014>even better when the expose puts her in the same orbit as a magazine publisher whose blackmailing schemes led to the death of her beloved father. Appealing to a young Russian jeweler for help, Vera is unprepared when she begins falling in love with him<U+2026>and even more unprepared when she gets caught up in his deceptions and finds herself at risk of losing all she has worked so hard to achieve.